American party politics : essays and readings - Herzberg, Donald; Pomper , Gerald M. (New York, 1966)
Party politics has been described as America's leading team sport. Increasingly it is also the most important serious activity of the nation. The power of govern ment is now crucial to all our lives, and politics is the means of controlling that power. In writing this book author hope to aid students of all ages to understand the American party system.
Keywords: Political Parties